Academic Supervision toward Teacher’s Performance through Motivation as Intervening Variable - Hendro Prasetyono; Agus Abdillah; Dona Fitria (Intelektual Pustaka Media Utama, 2018)
The aims of this research were to find the effect of Academic Supervision of School Principal and Work Motivation toward Teacher’s Performance of Bussines and Management Group State’s and Private’s Vocational High School in Depok City directly or indirectly. The population of this research was Bussines and Management teachers in Depok City amounting to 384 people. The sample in this research amounted to 80 people. The sampling method was done by using proportionate random sampling. Data collection is done by filling questionaires. Analysis of the data used is path analysis. Data processing is performed with IBM SPSS version 23.0 for Windows. The results showed that there is significant influence between Academic Supervision of School Principal to Work Motivation (1), Academic Supervision of School Principal to Teacher’s Performance (2), and Work Motivation to Teacher’s Performance (3). Totally, the magnitude of the effect is known 68,39 % directly and indirectly, while the remaining 37,10% is influenced by other factors not examined in of this research.